Pathoetiology of pneumonic Gaddi goats in Himachal Pradesh - KUMAR, RAJIV; KATOCH, R C; SHARMA, MANDEEP; MAHAJAN, ARVIND; DHAR, PRASANJIT (The Indian Journal of Animal Sciences, 2014)
Lung tissues (190) of Gadeli goats were microbiologically and histopathologically processed. Lung tissues on histopathology showed varying degree of emphysema, congestion and focal areas of haemorrhages along with edema and polymorphonuclear cells infiltration and revealed Chlamydia psittaci both microbiologically, as well as by special staining by Wolback's Giemsa stain. Bacteria such as Actinomyces pyogenes and Streptococcus pyogenes were isolated from the lungs of other goats and revealed bronchiolitb. alveolar oedema, emphysema, atelectasis, congestion, haemorrhages along with serotibrinous exudates around bronchioles.